Respostas
respondido por:
1
Temos combinação e arranjo !
C x+2,4 = A x+1,3
(x+2)!/4!.(x+2-4)! = (x+1)!/(x+1-3)!
(x+2)!/4!.(x-2)! = (x+1)!/(x-2)! (usando propriedades de fatoriais)
(x+2).(x+1).(x).(x-1).(x-2)/4!.(x-2)! = (x+1).(x).(x-1).(x-2)!/(x-2)!
(x+2).(x+1).(x).(x-1)/4! = (x+1).(x).(x-1)
(x+2).(x+1).(x).(x-1) = (x+1).(x).(x-1).4!
(x+2).(x+1).(x).(x-1)/(x+1).(x).(x-1) = 4.3.2.1
(x+2) = 12 . 2
x+2 = 24
x = 24 - 2
x = 22 ok
C x+2,4 = A x+1,3
(x+2)!/4!.(x+2-4)! = (x+1)!/(x+1-3)!
(x+2)!/4!.(x-2)! = (x+1)!/(x-2)! (usando propriedades de fatoriais)
(x+2).(x+1).(x).(x-1).(x-2)/4!.(x-2)! = (x+1).(x).(x-1).(x-2)!/(x-2)!
(x+2).(x+1).(x).(x-1)/4! = (x+1).(x).(x-1)
(x+2).(x+1).(x).(x-1) = (x+1).(x).(x-1).4!
(x+2).(x+1).(x).(x-1)/(x+1).(x).(x-1) = 4.3.2.1
(x+2) = 12 . 2
x+2 = 24
x = 24 - 2
x = 22 ok
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás